Aktivitas Antibakteri Ekstrak Etanol Kulit Jeruk Nipis (Citrus aurantifolia (Christm) Swingle) Terhadap Staphylococcus aureus - Apri Yoci Ro Berlina; Nora Yanti Lumbangaol; Helen Anjelina Simanjuntak (Herbal Medicine Journal, 2023)
The use of herbal plants is currently being developed as traditional medicine. About 80% of the world's population still relies on natural medicines for their health needs. Especially in the treatment of infectious diseases caused by Staphylococcus aureus bacteria. Treatment can use natural ingredients such as lime peel waste. Lime peel has a higher concentration of flavonoids compared to other parts such as seeds, fruit, and lime juice, making lime peel has antibacterial power. The purpose of this study was to determine the effect of ethanolic extract of lime peel (Citrus aurantifolia (Christm.) Swingle) on the growth of Staphylococcus aureus bacteria and to determine the potential of ethanolic extract of lime peel (Citrus aurantifolia (Christm.) Swingle) as an antibacterial. The extraction method is by maceration using 96% ethanol solvent, while the antibacterial activity test is using the paper disc diffusion method. The results showed that the ethanolic extract of lime peel at concentrations of 10%, 30%, 50% and 70% had inhibition zone diameters of 7.31 mm, 7.67 mm, 9.00 mm and 12.63 mm, respectively. The conclusion of this study is that the ethanolic extract of lime peel is effective at a concentration of 70% with a strong category.